Oral carcinogenesis triggers a nociceptive behavior and c‐Fos expression in rats' trigeminal pathway. (13th March 2022) - Alves, Joana Maria dos Santos; Viana, Khalil Fernandes; Pereira, Anamaria Falcão; Lima Júnior, Roberto César Pereira; Vale, Mariana Lima; Pereira, Karuza Maria Alves; Gondim, Delane Viana
Abstract: Objective: To recognize changes that occur along the trigeminal pathway in oral cancer in order to establish an effective approach to pain control. Methods: Wistar rats were divided into control and 4‐NQO groups for 8, 12, 16, or 20 weeks. 4‐NQO suspension was administered on the animals' tongues. Mechanical hyperalgesia, assessment of facial expressions, and an open‐field test were performed. After euthanasia, the animals' tongues were removed for macro‐ and microscopic analysis. c‐Fos expression was analyzed in the trigeminal pathway structures. Results: 4‐NQO induced time‐dependent macroscopic lesions that were compatible with neoplastic tumors. Histopathological analysis confirmed oral squamous cell carcinoma in 50% of the animals on the 20th week. There was a significant nociceptive threshold reduction during the first two weeks, followed by a threshold return to the baseline levels, decreasing again from the 12th week. Facial nociceptive expression scores were observed on the 20th week, while increased grooming and exploratory activity were observed on the 8th week. Trigeminal ganglion showed an increased c‐Fos immunoexpression on the 20th week, and in the trigeminal subnucleus caudalis, it occurred on the 16th and 20th. The long‐term carcinogenic exposure caused changes in the nociceptive behavior and c‐Fos expression in the rats' trigeminal pathway.